Interpretation of elevated baseline concentrations and serial changes of high-sensitivity cardiac troponin T in confirmed muscular dystrophies - Yildirim, Mustafa; Reich, Christoph; Salbach, Christian; Pribe-Wolferts, Regina; Milles, Barbara Ruth; Täger, Tobias; Müller-Hennessen, Matthias; Weiler, Markus; Meder, Benjamin; Frey, Norbert; Giannitsis, Evangelos (ESC heart failure, 2024)
Aims Concentrations of high-sensitivity cardiac troponin T (hs-cTnT) are frequently elevated in stable patients with confirmed muscle dystrophies. However, sparse information is available on the interpretation of serial concentration changes. Methods Hs-cTnT was collected in 35 stable outpatients with confirmed skeletal muscle dystrophies at 0 and 1 h and after 6-12 months during scheduled outpatient visits. We simulated the effectiveness of the European Society of Cardiology (ESC) 0/1 h algorithm and assessed biological variation at 6-12 months using two established methods: reference change value (RCV) and minimal important difference (MID). Results Median baseline hs-cTnT concentrations were 34.4 ng/L [inter-quartile range (IQR): 17.5-46.2], and values > 99th percentile upper limit of normal were present in 34 of 35 patients. All patients were stable without cardiovascular adverse events during a follow-up of 6.6 months (IQR: 6-7). Median concentration change was 1.9 ng/L (IQR: 0.7-3.2) and 0.8 ng/L (IQR: 0-7.0) at 60 min and 6-9 months, respectively. Applying the criteria of the ESC 0/1 h algorithm for triage of suspected acute coronary syndrome (ACS) showed poor overall effectiveness of baseline hs-cTnT values. No patient would qualify for rule-out based on hs-cTnT less than the limit of detection, whereas five cases would qualify for rule-in based on hs-cTnT ≥ 52 ng/L. Biological variabilities at 6-12 months per MID and RCV were 1.2 ng/L [95% confidence interval (CI): 0.7-2.1] and 28.6% (95% CI: 27.9-29.6), respectively. A total of 8 (22.9%) and 25 (71.4%) cases exceeded the biological variation range, suggesting some additional myocardial damage. Conclusions The high prevalence of elevated hs-cTnT could negatively impact the effectiveness of rule-out and rule-in strategies based on a single hs-cTnT value. Knowledge of the physiological and biological variation of hs-cTnT after 6-12 months is helpful to detect the progression of cardiac involvement or to search for cardiac complications including but not limited to arrhythmias that may trigger acute or chronic myocardial damage.
Online veröffentlicht: 11. Juni 2024
Gesehen am 28.01.2025